Brønsted Acid Promoted Reduction of Tertiary Phosphine Oxides. Issue 14 (9th June 2017) - Krachko, Tetiana; Lyaskovskyy, Volodymyr; Lutz, Martin; Lammertsma, Koop; Slootweg, J. Chris
Abstract : Recently, Brønsted acids, such as phosphoric acids, carboxylic acids, and triflic acid, were found to catalyze the reduction of phosphine oxides to the corresponding phosphines. In this study, we fully characterize the HCl, HOTf, and Me2 SiHOTf adducts of triphenylphosphine oxide and find that the thermally stable adduct Ph3 POH + OTf – is efficiently converted into triphenylphosphine at 100 °C in the presence of readily available hydrosiloxanes. Under the same reaction conditions, also Ph3 POSiMe2 H + OTf – selectively affords triphenylphosphine indicating that silylated phosphine oxides are likely intermediates in this process. Abstract :